A role for the extracellular matrix component hyaluronan in kidney dysfunction during ACE‐inhibitor fetopathy. (26th January 2015) - Hansell, P.; Palm, F.
Abstract Despite data showing that inhibitors of the renin‐angiotensin system increase the risks of fetal morbidity and dysfunctionality later in life, their use during pregnancy has increased. The fetopathy induced by angiotensin converting enzyme (ACE) inhibitors is characterized by anuria, hypotension and growth restriction, but can also be associated with pulmonary hypoplasia. In the kidney, this fetopathy includes atrophy of the medulla, reduced number of glomeruli, developmental lesions of tubules and vessels, tubulointerstitial inflammation and extracellular matrix accumulation. Although angiotensin II (Ang II) inhibition during nephrogenesis interferes with normal growth and development, this review will focus on effects of the heavily accumulated matrix component hyaluronan (HA). An important mechanism of HA accumulation during nephrogenesis is disruption of its normal reduction as a consequence of lack of Ang II activation of hyaluronidase. Hyaluronan has very large water‐attracting properties and is pro‐inflammatory when fragmented. The ensuing inflammation and interstitial oedema affect kidney function. Hyaluronan is colocalized with CD44 overexpression and infiltrating immune cells. These properties make HA a plausible contributor to the observed structural and functional kidney defects associated with the fetopathy. Available data support an involvement of HA in kidney dysfunction of the foetus and during adulthood due to the physico‐chemical characteristics of HA. No clinical treatment for HA accumulation exists. Treatment with the HA‐degrading enzyme hyaluronidase and an HA synthesis inhibitor has been tested successfully in experimental models in the kidney, heart and pancreas. Reduced HA accumulation to reduce interstitial oedema and inflammation may improve organ function, but this concept needs to be tested in a controlled study before causal relationships can be established.